Respiratory muscle dysfunction in congestive heart failure - Meyer, Franz Joachim; Borst, Mathias M.; Zugck, Christian; Kirschke, Andreas Erich; Schellberg, Dieter; Kübler, Wolfgang; Haass, Markus (Circulation, 2001)
In congestive heart failure (CHF), the prognostic significance of impaired respiratory muscle strength has not been established.